SAINS (Studi Al-Qur’an Intensif): Pemberdayaan Literasi Qur’ani Mahasiswa UNM melalui Program Baca Tulis Al-Qur’an - Ushwa Dwi Masrurah Arifin Bando; Irwansyah Suwahyu (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was carried out in the form of the Studi Al-Qur’an Intensif (SAINS) program as an effort to empower Qur’anic literacy among students of Universitas Negeri Makassar. The program focused on improving the ability to read and write the Qur’an, considering that some students still lacked the skill to read properly and correctly according to the rules of tajwīd. The implementation methods included a preliminary test of Qur’anic reading and writing skills, intensive mentoring through study groups, the application of the talaqqī method, and periodic evaluation through a final test. The results showed a significant improvement in students’ ability to read and write the Qur’an, a strengthened understanding of basic tajwīd, and an increased spiritual motivation to become closer to the Qur’an. In addition, the program successfully fostered a collaborative and sustainable Qur’anic learning atmosphere within the campus environment. Thus, SAINS proved to be an effective means of empowering students’ Qur’anic literacy while instilling religious values as a provision for both academic and social life.